2014 IEEE International Conference on Services Computing 2014
DOI: 10.1109/scc.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

SaaS Architecture and Pricing Models

Abstract: Abstract-In the new era of computing, SaaS software with different architectural characteristics might be priced in different ways. Even though both pricing and architectural characteristics are responsible for the success of the offering; the relationship between architectural and pricing characteristics has not been studied before. The present study fills this gap by employing a multi-case research. The findings accentuate that flexible and well-designed architecture enables different pricing models; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 26 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…He found that software renting in the SaaS model leads to greater investments in product development and consequently to higher software quality. In a more recent study, Laatikainen and Ojala (2014) investigated how SaaS architecture impacts on opportunities to use different pricing models among SaaS providers. They found that scalability and high levels of modularity brought opportunities to apply a greater variety of pricing models.…”
Section: Opportunities Provided By Cloud Servicesmentioning
confidence: 99%
“…He found that software renting in the SaaS model leads to greater investments in product development and consequently to higher software quality. In a more recent study, Laatikainen and Ojala (2014) investigated how SaaS architecture impacts on opportunities to use different pricing models among SaaS providers. They found that scalability and high levels of modularity brought opportunities to apply a greater variety of pricing models.…”
Section: Opportunities Provided By Cloud Servicesmentioning
confidence: 99%
“…Price discrimination refers to a pricing model in which the same product is offered to different customers at different prices [16,17,20,21]. The price discrimination model can be divided into first-degree, second-degree, and third-degree price discrimination.…”
Section: B Pricing Models In Software Businessmentioning
confidence: 99%
“…customers are charged based on the number of transactions they perform) and premium based revenue (users are charged for premium versions besides the free versions) [13,16,48]. Irrespective of the pricing structure an SP adopts, a reliable estimate of the infrastructure costs it has to sustain to provide the service is required in order to ensure the existence of adequate margins [37]. This process has become more and more important for SPs due to increasing competition in the cloud environment, where SPs are sometimes forced to deliver services whose costs exceed revenues [17].…”
Section: Introductionmentioning
confidence: 99%